2022
DOI: 10.1111/epi.17274
|View full text |Cite
|
Sign up to set email alerts
|

International consensus on diagnosis and management of Dravet syndrome

Abstract: Objective: This study was undertaken to gain consensus from experienced physicians and caregivers regarding optimal diagnosis and management of Dravet syndrome (DS), in the context of recently approved, DS-specific therapies and emerging disease-modifying treatments.Methods: A core working group was convened consisting of six physicians with recognized expertise in DS and two representatives of the Dravet Syndrome Foundation. This core group summarized the current literature (focused on clinical presentation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 21 publications
3
109
0
3
Order By: Relevance
“…The ketogenic diet is moderately effective for seizure control and could also be considered as second line management in patients with suboptimal response to clobazam and valproic acid. Recent studies also show that newer medications like cannabinoids and fenfluramine would be beneficial in conditions where first-line medications do not help [18] , [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%
“…The ketogenic diet is moderately effective for seizure control and could also be considered as second line management in patients with suboptimal response to clobazam and valproic acid. Recent studies also show that newer medications like cannabinoids and fenfluramine would be beneficial in conditions where first-line medications do not help [18] , [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, further studies involving professionals from a wider range of disciplines involved in the care and management of patients with DS, such as social workers or therapists, may provide a more accurate view on the management of PROs in the daily life of DS patients and their families. Another limitation of the study associated to the Delphi technique is related to the consensus definition, which is not standard, and therefore, different criteria can be found in the literature (23,29). For this reason, we deemed appropriate to define two categories of consensus, moderate and strong (29).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of the study associated to the Delphi technique is related to the consensus definition, which is not standard, and therefore, different criteria can be found in the literature (23,29). For this reason, we deemed appropriate to define two categories of consensus, moderate and strong (29). We considered that although agreement was reached on most of the items consulted, those that fell into the moderate consensus category may have raised more controversy among the experts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple rigorous RCTs have shown that FFA is highly efficacious against Dravet syndrome-associated convulsive seizures and, to a lesser degree, against LGS-associated drop seizures. An international consensus on the management of Dravet syndrome noted FFA as a possible first-line therapy with moderate to strong consensus among physicians and caregivers [ 93 ]. Both physicians and caregivers rated it as an agent with excellent tolerability.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%